Fungos micorrízicos arbusculares, substrato, fósforo e manejo da irrigação na produção de mudas de Cedrela fissilis Vell. - Santos, Lacy Antonia Dos (2020)
Cedrela fissilis Vell. is a tree species of ecological and economic importance in Brazil. It is currently vulnerable to extinction, being of paramount importance the development of technologies that seek greater efficiency in the process of seedling production. The arbuscular mycorrhizal fungi (FMAs), phylum Glomeromycotina, form obligatory symbiotic associations with the roots of the majority of vascular plants. It was hypothesized that these associations are promising alternatives to influence the physiological processes of plants, and thereby benefit their productivity. Thus, in article one (1), the objective was to evaluate the effect of using an inoculum substrate containing arbuscular mycorrhizal fungi of the species Acaulospora longula (Al) and Claroideoglomus etunicatum (Ce) altogether with a commercial organic substrate on the growth and physiology of C. fissilis seedlings. In article two (2), the objective was to evaluate the effect of inoculation with arbuscular mycorrhizal fungi of the species Acaulospora longula and Claroideoglomus etunicatum, phosphorus doses and different irrigation management on the growth and physiological responses of C. fissilis seedlings. The parameters evaluated included: dry biomass, gas exchange, chlorophyll content (SPAD index), photosynthetic performance, number of spores, and percentage of root colonization. The results found in the first experiment demonstrated that the inoculation of Al and Ce in C. fissilis associated with the organic substrate composed of pine bark increased physiological parameters such as stomatal conductance and transpiration, resulting in an even higher chlorophyll content, however assimilation of carbon and the accumulation of biomass did not vary according to the treatments. The absence of organic substrate results in lower values for the variables stomatal conductance and transpiration. The increase in the percentage of inoculum substrate (in the inoculum: organic compound mixture) led to an increase in the number of spores and the percentage of root mycorrhizal colonization. In the second experiment, the results corroborated the hypothesis that in the production of C. fissilis seedlings the accumulation of dry biomass and physiological parameters are influenced by inoculation with FMAs, doses of P, and frequency of irrigation, although the effects vary according to the species of AMF inoculated. The best combination for producing seedlings with greater biomass and greater synergism between plant-microorganism occured in the inoculation with Ce at the dose of 30 mg dm-3 of P replenishing water 1x a week. The benefits of inoculation with FMAs correlated with greater efficiency of photosystem II and chlorophyll content in the inoculated seedlings.